Developing a Weight-Neutral Health Intervention in Denmark: Protocol for a Co-Design Process - Lene Meyer; Rasmus Køster-Rasmussen; Ann-Kathrin Lindahl Christiansen; Berit Lilienthal Heitmann; Gitte Kingo Vesterlund; Sofus Christian Larsen; Ina Olmer Specht; Fanney Thorsteinsdottir; Emma Katrine Frøhlke Steinbo; Clara Lundmark Appel; Gudrun Agusta Sigurdardottir; Susanne Reventlow; et al. (JMIR Public Health and Surveillance)
Abstract BackgroundLifestyle interventions for weight loss are generally ineffective in achieving clinically meaningful long-term reductions in body weight and may contribute to negative behavior such as weight cycling or disordered eating. Negative focus on high weight may also contribute to weight stigma. Weight stigma includes negative attitudes and discriminatory behavior toward people with big bodies and can result in psychological stress and unfavorable health outcomes. Taken together, it is possible that the potential harms of lifestyle-based weight loss interventions may exceed the potential benefits. Weight-neutral health (WNH) has emerged as an alternative strategy advocating for size diversity, intuitive eating, and joyful physical movement, all without placing emphasis on weight reduction. ObjectiveThis protocol outlines the study design for the co-design process of developing a WNH complex intervention, engaging relevant stakeholders in Denmark. MethodsWe base our understanding of WNH on the principles from Health at Every Size: body acceptance, joyful movement, intuitive eating, and weight stigma reduction. The co-design development process is based on the Medical Research Council’s framework for complex interventions and applies methods from human-centered design through 4 iterative design phases of engaging stakeholders—discoverdefine2design2validat ResultsThe project is fully funded. As of August 2024, the co-design process was in the closing phase. In total, 15 HPs were included, some of whom have larger body sizes. This provides a dual perspective, combining their personal experiences of living with a high BMI with their professional expertise. In total, 16 people with BMI≥30 kg/m2 ConclusionsThe intervention designed in and from the co-design process will be tested for feasibility in 2025. The findings from the feasibility study will inform a future randomized controlled trial and present novel findings in the field of health management. The long-term goal is to implement the intervention in a Danish municipal setting free of charge.